Determinants of customer satisfaction and loyalty in the Turkish e-commerce sector - Yalçınkaya, Mehmet; Çataldaş, İbrahim (Frontiers in Communication, 2025)
IntroductionThe rapid development of digital technologies has significantly transformed consumer behavior, making social media platforms essential marketing tools. However, there is a notable gap in the literature regarding the combined effects of social media marketing, price promotions, and corporate social responsibility (CSR) attitudes on customer satisfaction and loyalty in e-commerce.MethodsA quantitative research design was adopted. Data were collected from 761 e-commerce customers in Turkey who are active social media users. Validated scales from the literature were used, and structural equation modeling (SEM) was applied for data analysis.ResultsThe findings indicate that social media marketing and price promotions have a significant positive impact on customer satisfaction and loyalty. Attitudes toward CSR positively affect customer satisfaction but do not have a direct effect on customer loyalty.DiscussionThe study enriches the literature on digital consumer behavior by integrating CSR into loyalty models and emphasizing the mediating role of satisfaction. Practical recommendations are provided for e-commerce businesses. Future research is encouraged to explore cultural differences and sector-specific dynamics in social media marketing and promotional strategies.